Swallowing and Aspiration: How Much Is Affected by the Number of Arytenoid Cartilages Remaining After Supracricoid Partial Laryngectomy? - Caner Kılıç; Ümit Tunçel; Metin Kaya; Ela Cömert; Samet Özlügedik (Clinical and Experimental Otorhinolaryngology, 2017)
Objectives The aim of this study was to compare the effect of the presence of one or two arytenoids on early/late period swallowing-aspiration functions. Methods Supracricoid partial laryngectomy (SCPL) with the diagnosis of laryngeal cancer between 2012 and 2014 were retrospectively evaluated. The patients were categorized into two groups as follows: group I, patients who underwent SCPL with one arytenoid cartilage and group II, patients who underwent SCPL with two arytenoid cartilages. The time of decannulation and oral feeding onset, and swallowing-aspiration functions were evaluated and compared in the early nutritional period, first, and third months. Results There was no significant correlation between decannulation time and swallowing-aspiration. The aspiration rates in group I and group II were similar and there was no significant difference in oral feeding onset and aspiration grades in the first and third months between both groups. Conclusion We found similar oncological and functional outcomes in SCPL which protected one or two arytenoid cartilages. Therefore we suggest to be performed one arytenoid cartilage SCPL in selected patients who was advance stage and tumor volume over with larynx cancer.